Financial accounting - Weygandt, Jerry J. (John Wiley & Sons, 2000)
Accounting in action. The recording process. Adjusting the accounts. Completion of the accounting cycle. Accounting for merchandising operations. Inventories. Accounting principles. Internal control and cash. Accounting for receivables...